A benchmark for Monte Carlo simulation in gamma-ray spectrometry. (December 2019) - Lépy, M.C.; Thiam, C.; Anagnostakis, M.; Galea, R.; Gurau, D.; Hurtado, S.; Karfopoulos, K.; Liang, J.; Liu, H.; Luca, A.; Mitsios, I.; Potiriadis, C.; et al.
Abstract: Monte Carlo (MC) simulation is widely used in gamma-ray spectrometry, however, its implementation is not always easy and can provide erroneous results. The present action provides a benchmark for several MC software for selected cases. The examples are based on simple geometries, two types of germanium detectors and four kinds of sources, to mimic eight typical measurement conditions. The action outputs (input files and efficiency calculation results, including practical recommendations for new users) are made available on a dedicated webpage. Highlights: Examples of the use of Monte Carlo simulation using different software. Simple cases with two types of germanium detectors and four kinds of sources. Calculation of full-energy peak and total efficiencies for 5 energies. Input files and efficiency calculation results available on a dedicated webpage.